2015
DOI: 10.1093/conphys/cov045
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, activity behaviour and body mass in captive parrots

Abstract: Captive breeding programmes are common for many parrot species. We show that in small parrots kept in standard cages with ad libitum food, high weight gain was prevalent and linked with a risk of DNA damage. Such damage could explain the poor health, fertility and survival of many captive parrots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
9
1
Order By: Relevance
“…However, total superoxide dismutase (SOD) activity increased in the lower animals. In another study, it was found that active behavior in parrots was associated with oxidative damage and that the DNA damage of active budgerigars was greater than that of sedentary birds (Larcombe et al, 2015). Increased SOD levels due to a possible oxidative stress in this study were similar to those of Almeida et al (2009), but the increase in GPx levels did not overlap with the results of the study.…”
Section: Discussionsupporting
confidence: 55%
“…However, total superoxide dismutase (SOD) activity increased in the lower animals. In another study, it was found that active behavior in parrots was associated with oxidative damage and that the DNA damage of active budgerigars was greater than that of sedentary birds (Larcombe et al, 2015). Increased SOD levels due to a possible oxidative stress in this study were similar to those of Almeida et al (2009), but the increase in GPx levels did not overlap with the results of the study.…”
Section: Discussionsupporting
confidence: 55%
“…In a study of domesticated budgerigars, birds were given ad libitum food and confined to cages that limited exercise. High body mass at the end of 28 days correlated with more DNA damage (Larcombe et al ., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The same species was used to test the effects of fenvalerate insecticide indicating significant DNA-damaging effects in bone marrow cells compared to control birds [320]. Small parrots such as budgerigars (Melopsittacus undulatus) that are usually kept in captivity were used for the assessment of DNA-damaging effect in relation to behavioural activity and dietary habits [321,322]. Moreover, wild-caught captive greenfinches (Carduelis chloris) and common yellowthroat (Geothlypis trichas) were used to test the DNA-damaging effects of paraquat and carotenoid-based sexual ornamentation, respectively [323,324].…”
Section: Birdsmentioning
confidence: 99%